Expectations on Hierarchical Scales of Discourse: Multifractality Predicts Both Short- and Long-Range Effects of Violating Gender Expectations in Text Reading. Issue 1 (2nd January 2018) - Booth, Chase R.; Brown, Hannah L.; Eason, Elizabeth G.; Wallot, Sebastian; Kelty-Stephen, Damian G.
Abstract : Reader expectations form across hierarchical scales of discourse (e.g., from coarse to fine: genre, narrative, syntax). Cross-scale interactivity produces word reading times (RTs) with multifractal structure. After introducing multifractals, we test two hypotheses regarding their relevance to reader expectations: (1) multifractal evidence of cross-scale interactions from RTs preceding violation of expectations would interact with mean reading speed to predict RTs immediately after the expectation violation and (2) postsurprise RTs would exhibit stronger cross-scale interactions. Thirty-four adult participants read one of two 2, 000-word stories that used gender stereotypes to suggest that an ambiguously named protagonist was male. However, the stories postponed gender information until word 1, 000: male in one story and female in the other. For slower readers, cross-scale interactions accentuated postreveal slowing but also minimized subsequent pausing over 15 postreveal RTs. Surprise strengthened cross-scale interactions over all postsurprise RTs. These results suggest that multifractality may index anticipation across multiple scales of discourse.